2022
DOI: 10.55627/agrivet.01.01.0242
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis and Heterosis Studies in 5×5 Diallel Crosses of Maize under the Meteorological Conditions of Rawalakot

Abstract: This experiment was performed to evaluate heterosis and combining ability of morphological traits in maize (Zea mays L.). The experiment was arranged in randomized complete block design (RCBD) with three replicates. Twenty maize hybrids were obtained by 5×5 complete diallel crosses in first year and were evaluated for plant attributes like plant height, ear height, ear leaf area, flag leaf area, days to 50% silking, days to 50% pollen shed, anthesis-silking interval (ASI), no. of leaves per plant, no. of branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…These findings align with prior research on maize heterosis. Here, better parent heterosis results are in correspondence with Kumawat et al (2020) [9] ; Sabitha et al (2021) [16] ; Yadav and Gangwar (2021) [24] ; Kamal et al (2022) [7] ; Mogesse et al (2022) [13] ; Shafiq-Ur-Rehman et al (2022) [20] .…”
Section: Number Of Kernel Per Rowsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings align with prior research on maize heterosis. Here, better parent heterosis results are in correspondence with Kumawat et al (2020) [9] ; Sabitha et al (2021) [16] ; Yadav and Gangwar (2021) [24] ; Kamal et al (2022) [7] ; Mogesse et al (2022) [13] ; Shafiq-Ur-Rehman et al (2022) [20] .…”
Section: Number Of Kernel Per Rowsupporting
confidence: 78%
“…Over Phule Maharshi, DML-1336 x DML-1112 (24.84%), DML-1336 x DS-NP/R-8-42 (24.08%), and 52099 x DML-1112 (23.24%) showed highly significant positive heterosis. Better parent results were in tune with Onejeme et al (2020) [14] ; Vinoth et al (2021) [23] ; Pawar et al, (2021) [15] ; Sabitha et al (2021) [16] ; Yadav and Gangwar (2021) [24] ; Shafiq-Ur-Rehman et al (2022) [20] reported mid parent, better parent and standard heterosis for this trait in maize.…”
Section: Kernel Yield Per Plant (G)mentioning
confidence: 54%